Pengaruh Pertumbuhan Ekonomi, Inflasi, dan Nilai Tukar terhadap Profitabilitas Bank Syariah dan Bank Konvensional di Indonesia dengan BI-Rate sebagai Intervening - Rika Rizkia; Novi Mubyarto; Hamdi Zas Pendi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze and compare the effects of macroeconomic variables, namely Economic Growth, Inflation, and Exchange Rate, on the profitability of Islamic Commercial Banks and Conventional Commercial Banks in Indonesia during 2019–2025, both directly and indirectly through the Bank Indonesia Interest Rate (BI Rate) as an intervening variable. This quantitative study employs path analysis, with hypothesis testing based on path coefficients, t-statistics, and p-values. The results show that Economic Growth and Exchange Rate have positive and significant effects on the BI Rate, while Inflation has no significant effect. For Islamic Commercial Banks, Economic Growth and Exchange Rate have positive and significant effects on profitability, whereas Inflation has no significant effect. The BI Rate has a negative and significant effect on Islamic banks' profitability and significantly mediates the effects of Economic Growth and Exchange Rate in a negative direction. For Conventional Commercial Banks, Economic Growth, Inflation, and Exchange Rate have positive and significant effects on profitability, while the BI Rate has a positive but insignificant effect. Furthermore, the BI Rate does not significantly mediate the effects of the three macroeconomic variables on conventional banks' profitability. These findings indicate differences in monetary policy transmission and macroeconomic sensitivity between Islamic and conventional banking sectors in Indonesia.